COVID‐19 in older adults: Retrospective cohort study in a tertiary hospital in Japan. Issue 11 (13th September 2020) - Sano, Tomoya; Kimizuka, Yoshifumi; Fujikura, Yuji; Hisada, Tetsuya; Watanabe, Chie; Suematsu, Ryohei; Izumi, Kaori; Sugiura, Hiroaki; Miyata, Jun; Shinmoto, Hiroshi; Nagata, Masayoshi; Kawana, Akihiko
Abstract : Aim: We aimed to describe the clinical characteristics, treatment and outcomes of patients with COVID‐19 pneumonia, in particular older patients, admitted to tertiary and partner hospitals in Saitama, Japan. Methods: We retrospectively reviewed the medical records of patients with COVID‐19 pneumonia admitted to tertiary and partner hospitals in Saitama, Japan. Twenty‐six patients with COVID‐19 were categorized into two groups, i.e., older (≥75 years) and younger adults (≤74 years). We evaluated the clinical characteristics, comorbidities, symptoms, laboratory test results, treatments and outcomes of the patients. Results: The majority of the older patients had comorbidities, such as dementia, cardiovascular disease and bone fractures. Comorbidities were significantly more frequent in older patients than younger patients. No association was found between age and body temperature or the incidence of respiratory failure. White blood cell count was significantly lower in older patients ( P = 0.018) and the decrease in lymphocytes was greater in younger patients ( P = 0.009). Computed tomography (CT) of all patients showed non‐segmental, peripherally dominant ground‐glass opacities consistent with COVID‐19 pneumonia. In older patients, antiviral drugs, anticoagulants and anti‐inflammatory drugs were administered on a compassionate use basis. The difference in mortality between the older and the younger patients was not statistically significant. Conclusions: In older patients, typical clinical symptoms and blood test changes were often absent; however, CT always contained typical findings of COVID‐19, suggesting that CT may be a useful diagnostic tool. Our report illustrates that appropriate treatment, taking patient background into consideration, may improve their condition regardless of age. Geriatr Gerontol Int 2020; 20: 1044–1049 .